Characterization of mechanical properties of wood of clones of Hevea brasiliensis (Willd. Ex Adr.) - De Lima, Israel Luiz; Bergamo, Rafaela; Bermudez, Karen Rizzato; De Moraes, Mario Luiz Teixeira [UNESP]; Garcia, José Nivaldo (Instituto de Pesquisa e Estudos Florestais (IPEF), 2020)
The rubber tree is a native species of Brazil, whose occurrence is characteristic of the Amazonian forest, but easily adaptable in most of the national territory. The main use of the rubber tree is the extraction of latex, whose cycle is economically viable for 25 years, and the wood, after cutting, is usually destined for energy use. In order to use it industrially, this study aims to select clones of H. brasiliensis, characterizing their mechanical properties of wood. The experiment was installed in 1982 at the Faculty of Engineering of Ilha Solteira / UNESP, located in Selvíria, MS. The experimental design was a randomized block, composed of five treatments (clones), with 5 replicates and linear plots of 10 plants, at a spacing of 8m × 2.5m. We sampled 25 trees, five of each clone, chosen within each block. When analyzing the mechanical properties, it is possible to observe a variation between the clones where the clone RRIM 600 is highlighted by the highest values, and the clones IAN 717 and GT1 with the lowest values. The results verified can subsidize the information for comparative effect with some species used commercially for structural purposes.
Keywords: Mechanical strength.; Quality of wood; Rubber